Primary mucinous adenocarcinoma of the bladder with signet-ring cells: case report - Marques, Marcelo Lorenzi; D’Alessandro, Gabriel Salum; Chade, Daher Cezar; Lanzoni, Valéria Pereira; Saiovici, Samuel; Almeida, Cláudio José Ramos de (São Paulo Medical Journal, 2007)
CONTEXT: Primary adenocarcinomas of the bladder are uncommon and usually occur by contiguity with or hematogenic dissemination of other adenocarcinomas such as colorectal, prostate and gynecological tract carcinomas. Mucinous and signet-ring cell histological patterns are even rarer and it is often diffi cult to morphologically distinguish them from metastatic colorectal adenocarcinoma. CASE REPORT: We present and discuss a rare case of primary mucinous adenocarcinoma of the bladder with signet-ring cells in a 57-year-old male patient. Other primary sites for the tumor had been excluded and, in the absence of digestive tract tumor and for confi rmation that it was a primary bladder tumor, an immunohistochemistry study was performed.